CHARACTERISTICS OF THE ACTIVITY OF METASEARCH SYSTEMS - Gulhayo Panjiyeva (Modern American Journals, 2025)
The article analyzes the role of metasearch systems in the information search process, their functional structure, algorithmic principles of operation, and their advantages over traditional search systems. The architecture of the systems, user interface, query routing, and result integration modules are considered from a technical point of view. The final part analyzes the future development prospects and scientific problems for modern metasearch systems based on artificial intelligence.
Keywords: Metasearch, LTR, syntactic analysis, semantic analysis, CTR, BERT, RoBERTa, cosine similarity, BM25, queries